Dukungan Anggota Keluarga dan Activity Of Daily Living (ADL) pada Penderita Post Stroke di Klinik Utama Graha Medika Salatiga - Rosiana Eva Rayanti; Kukuh Pambuka Putra; Meldy Enggelina Nenobanu - UKSW Salatiga (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2018)
Abstract: Indonesia Basic Health Research Data shows that the number of stroke patients diagnosed by health care practitioner increased from 8.3/1000 (2007) to 12.1/1000 (2013). After the stroke, the patient experiences physical, psychological, and social weakness in a long-term recovery process. As a result, the patient becomes partially or even completely dependent on others in performing daily activities. The member of family would accompany and care for the patient during their recovery period. This study aims to identify the relationship between family support and activity of daily living (ADL) in post-stroke patients at Graha Medika Salatiga Clinic. Correlation bivariate quantitative with random sampling technique is used in this research. The sample size was determined by the slovin formula. Data were analyzed using Spearman Rank correlation test. The results showed that family support (0.005) and ADL (0.009) normality test was significant. Majority of family members' support (53.28%) and ADL post-stroke patients (67.21%) were quite good. The relationship between the two variables above is strong with a correlation value of 0.730 and the correlation coefficient interval rs value 0.60-0.80 (strong relationship). The higher the support of family members, the more fulfilled the needs of ADL in patients with post-stroke.Keywords: Activity of Daily Living (ADL), Family Membership Support, Post-Stroke Patient Abstrak: Data Riset Kesehatan Dasar menunjukkan jumlah penderita stroke yang pernah di diagnosis oleh layanan kesehatan dan gejala meningkat dari 8,3 per1000 (2007) menjadi 12,1 per1000 (2013). Setelah mengalami stroke, penderita mengalami kelemahan fisik, psikis, dan sosial dengan proses pemulihan yang membutuhkan waktu panjang. Akibatnya, penderita menjadi sebagian atau bahkan sepenuhnya ketergantungan pada orang lain dalam melakukan aktivitas sehari-hari. Keluarga adalah orang yang mendampingi dan merawat penderita selama masa pemulihan. Tujuan penelitian ini untuk mengidentifikasi hubungan antara dukungan keluarga dengan activity of daily living (ADL) pada penderita paska stroke di Klinik Utama Graha Medika Salatiga. Metode yang digunakan ialah kuantitaf bivariat kolerasi dengan teknik random sampling. Sampel ditentukan dengan rumus slovin. Data dianalisa dengan uji korelasi Spearman Rank. Hasil menunjukkan uji normalitas dukungan keluarga (0,005) dan ADL (0,009) adalah signifikan. Mayoritas dukungan anggota keluarga (53,28%) dan ADL penderita paska stroke ialah (67,21%) adalah cukup baik. Hubungan antara kedua variabel di atas ialah kuat dengan nilai korelasi 0,730 dengan interval koofisien korelasi nilai rs 0,60-0,80 (hubungan kuat). Semakin tinggi dukungan anggota keluarga, maka semakin terpenuhi kebutuhan ADL pada penderita paska stroke.Kata kunci : Dukungan Anggota Keluarga, Activity of Daily Living (ADL), Penderita Paska Stroke